A case study of international notarization cooperation in private international law: a notarized power of attorney signed by a French citizen to accept a real estate gift - Zhang, Zheng; Cai, Yong (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This case reflects how Chinese notaries and French notaries cooperate to provide highquality legal services for the parties in the background of global epidemic.